2023
DOI: 10.1108/pm-11-2022-0086
|View full text |Cite
|
Sign up to set email alerts
|

Composite property price index forecasting with neural networks

Xiaojie Xu,
Yun Zhang

Abstract: PurposeThe Chinese housing market has gone through rapid growth during the past decade, and house price forecasting has evolved to be a significant issue that draws enormous attention from investors, policy makers and researchers. This study investigates neural networks for composite property price index forecasting from ten major Chinese cities for the period of July 2005–April 2021.Design/methodology/approachThe goal is to build simple and accurate neural network models that contribute to pure technical fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 134 publications
0
1
0
Order By: Relevance
“…https://orcid.org/0000-0002-4452-1540 Notes a. In addition, we applied the BDS test 71 to the 10 steel price series and found that the p-values of the tests are all almost zero based on embedding dimensions of 2-10 and ϵ (distance used to test proximity of data points) values of 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 times the price series standard deviation, [72][73][74][75][76][77][78][79] indicating some non-linear patterns as found in many different commodity prices. 80-85 b. p = 10 and X t = (X 1,t X 2,t X 3,t X 4,t X 5,t X 6,t X 7,t X 8,t X 9,t X 10,t ) ′ in our example, where X 1,t , X 2,t , X 3,t , X 4,t , X 5,t , X 6,t , X 7,t , X 8,t , X 9,t and X 10,t are related to prices of the rebar, steel wire, plate, hot rolled coil, cold rolled plate, galvannealed sheet, seamless tube, welded tube, section and narrow strip, respectively.…”
Section: Xiaojie Xumentioning
confidence: 99%
“…https://orcid.org/0000-0002-4452-1540 Notes a. In addition, we applied the BDS test 71 to the 10 steel price series and found that the p-values of the tests are all almost zero based on embedding dimensions of 2-10 and ϵ (distance used to test proximity of data points) values of 0.5, 1.0, 1.5, 2.0, 2.5 and 3.0 times the price series standard deviation, [72][73][74][75][76][77][78][79] indicating some non-linear patterns as found in many different commodity prices. 80-85 b. p = 10 and X t = (X 1,t X 2,t X 3,t X 4,t X 5,t X 6,t X 7,t X 8,t X 9,t X 10,t ) ′ in our example, where X 1,t , X 2,t , X 3,t , X 4,t , X 5,t , X 6,t , X 7,t , X 8,t , X 9,t and X 10,t are related to prices of the rebar, steel wire, plate, hot rolled coil, cold rolled plate, galvannealed sheet, seamless tube, welded tube, section and narrow strip, respectively.…”
Section: Xiaojie Xumentioning
confidence: 99%